Chromosome numbers and molecular phylogenetics of some endemic orchid species (Orchidaceae) of Sri Lanka - Ariyarathne, Menaka; Yakandawala, Deepthi; Barfuss, Michael H. J.; Samuel, Rosabelle; Chase, Mark W. (Phytotaxa, 2025)
In Sri Lanka, Orchidaceae have not been investigated in detail with molecular phylogenetic or cytotaxonomic studies with reference to endemic species. To address this gap, we analysed phylogenetic relationships of 113 species including 15 endemics and five native species, of which cytological investigations of 12 species (nine endemics, three native) are provided for the first time. Data matrixes were produced for nuclear ribosomal ITS (nrDNA) and plastid matK, which we combined with sequences of non-native species from other studies. Parsimony and Baysian analyses were done to investigate the phylogenetic position of the endemic species. The endemics fell with congeneric non-native species in nearly all cases. Chromosome numbers obtained from this study and the literature were mapped on the phylogenetic tree. Chromosome number variation across the tree shows that polyploidy and dysploidy (ascending and descending) have played a role in genomic evolution of the endemic species.